2001
DOI: 10.1080/165019701750098867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscle Strengthening and Physical Conditioning Training on Temporal, Kinematic and Kinetic Variables During Gait in Chronic Stroke Survivors

Abstract: The purpose of this study was to evaluate the impact of a combined program of muscle strengthening and physical conditioning on gait performance in subjects with chronic stroke, using a single group pre- and post-test design. Thirteen subjects were recruited for the 10-week program (3 days/week), which consisted of warm-up, aerobic exercises, lower extremity muscle strengthening and cool-down. Data from cinematographic film and a force plate obtained during multiple walking trials were used in a four-segment k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…The findings of the present study build upon recent work demonstrating an association between changes in paretic ankle plantarflexor function and improved post-stroke walking speed 44,45 . These studies, consistent with the early work of Olney and colleagues 6 , provide insight into the biomechanical mechanisms that may underlie the improvements in propulsion observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the present study build upon recent work demonstrating an association between changes in paretic ankle plantarflexor function and improved post-stroke walking speed 44,45 . These studies, consistent with the early work of Olney and colleagues 6 , provide insight into the biomechanical mechanisms that may underlie the improvements in propulsion observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have shown that adults with stroke do not push effectively with their PF during gait [9,10,11]. FES for hemiplegic gait is typically delivered only to the ankle DF to correct 'foot drop' during the swing phase, thereby failing to address other important stance and swing phase post-stroke gait deficits at the hip and knee [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, it is an important outcome measure of locomotor rehabilitation because it reflects both physical performance and physiological changes, 14,15 remains reliable and sensitive to change even as recovery advances, 16 and is a predictor of health status 17 as well as quality of life. 15 Walking speed has been used as the primary outcome measure for many clinical trials of locomotor-related interventions for persons with stroke, such as exercise therapy, 18 lower extremity strength training, 19,20 functional electrical stimulation, 21 treadmill walking, 22,23 and locomotor training with treadmill and body weight support. 24,25 A recent meta-analysis demonstrated that these approaches, although very different, led to similar gains in walking speed.…”
Section: Assessment Of Task Performancementioning
confidence: 99%